Ergänzung des Picard’schen Satzes für einige Klassen bianalytischer Funktionen - Balk, M. B. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. Б. Балк. Уточнение теоремы Пикара для некоторых классов бианалитических функцийM. B. Balkas. Pikaro teoremos patikslinimas kai kurioms bianalizinių funkcijų klasėms